Productionof catalytic and non-catalytic gases from pyrolysis of municipal solid waste (MSW) - Obid, Tursunov (School of Environmental Engineering, 2012)
This study focused on gas production from pyrolysis process of municipal solid waste by using three types of catalysts (zeolite, raw dolomite and calcined dolomite).